Retrofitting coal‐fired power plants with biomass co‐firing and carbon capture and storage for net zero carbon emission: A plant‐by‐plant assessment framework. Issue 1 (27th October 2020) - Wang, Rui; Chang, Shiyan; Cui, Xueqin; Li, Jin; Ma, Linwei; Kumar, Amit; Nie, Yaoyu; Cai, Wenjia
Abstract: The targets of limiting global warming levels below 2°C or even 1.5°C set by Paris Agreement heavily rely on bioenergy with carbon capture and storage (BECCS), which can remove carbon dioxide in the atmosphere and achieve net zero greenhouse gas (GHG) emission. Biomass and coal co‐firing with CCS is one of BECCS technologies, as well as a pathway to achieve low carbon transformation and upgrading through retrofitting coal power plants. However, few studies have considered co‐firing ratio of biomass to coal based on each specific coal power plant's characteristic information such as location, installed capacity, resources allocation, and logistic transportation. Therefore, there is a need to understand whether it is worth retrofitting any individual coal power plant for the benefit of GHG emission reduction. It is also important to understand which power plant is suitable for retrofit and the associated co‐firing ratio. In order to fulfill this gap, this paper develops a framework to solve these questions, which mainly include three steps. First, biomass resources are assessed at 1 km spatial resolution with the help of the Geography Information Science method. Second, by setting biomass collection points and linear program model, resource allocation and supply chain for each power plants are complete. Third, is by assessing the life‐cycle emission for each power plant. In this study, Hubei Province in China is taken as the research area and study case. The main conclusions are as follows: (a) biomass co‐firing ratio for each CCS coal power plant to achieve carbon neutral is between 40% and 50%; (b) lower co‐firing ratio sometimes may obtain better carbon emission reduction benefits; (c) even the same installed capacity power plants should consider differentiated retrofit strategy according to their own characteristic. Based on the results and analysis above, retrofit suggestions for each power plant are made in the discussion. Abstract : To achieve net zero carbon emission target set out in the Paris Agreement, this study explores how to retrofit coal‐fired power plants with biomass co‐firing and carbon capture and storage, taking into consideration of the detailed parameters of each plant, road network map, biomass collection points, and spatial distribution of biomass, based on Geography Information System and Life Cycle Assessment framework. Hubei Province of China has been chosen as the case region. This study can provide targeted retrofitting suggestion for each coal power plant and provide a common methodological framework for other power plants to develop such retrofitting plans.